Analyzing Students' Engagement in Online Learning Environment - Isnaeni Wahab; Sitti Aisyah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2022)
Students' engagement is a supporting factor that has an important position in the online learning process to achieve a better and more effective quality of learning. So, this research aims to determine student engagement in online learning. This research used a qualitative descriptive method, and the sample was taken from the English Department Universitas Muslim Maros and consisted of 41 students. The researcher used questionnaires to analyze the students' engagement as a guideline for analyzing and interpreting data and interviews to support the data. The data from the questionnaire will be analyzed using the Likert Scale. The indicators used to measure student engagement in online learning included emotion, participation, behavior, cognition, and skill factors. The data shows that students generally support online education, which is well-received by students.